Populations with higher average intelligence are healthier, but do they smoke fewer cigarettes? - Ahmad Suhaimi, Siti Shazwani; Burhan, Nik Ahmad Sufian; Abdul Rahman, Abdul Razak; Daud, Mohd Najmi (Council for Social and Economic Studies, 2019)
Societies with high intelligence quotient (IQ) practice healthier lifestyles, which results in enhanced health status and higher life expectancy. This paper attempts to examine the impact of national average IQ on level of cigarette consumption at a cross-country level. Since smoking is detrimental for human health and causes about ten percent of the total number of deaths every year worldwide, this research is deemed important. Regression analysis with robust standard errors was employed to scrutinize the effect of national IQ on cigarette consumption. After controlling for demographic factors, IQ was found to have significantly positive associations with all measures of cigarette consumption. Unlike the control variables, the positive effect of IQ on smoking was found to be robust to spatial dependence. Nevertheless, the positive effect gradually reduced as the IQ level increased. The proposed explanation is that cigarette smoking is an evolutionarily novel activity that did not previously exist in human ancestral environments. Therefore, as the IQ level rises, societies initially are more likely to appreciate and adopt the novel behavior of smoking. In high-IQ societies, the positive relationship eventually weakens as people become more aware of the health hazards of smoking.